Encouraging Purchase Intention in TikTok Live Streaming: The Role of Live Streaming Shopping Attributes - Chan, Syafruddin; Asni, Kurnia (Universitas Syiah Kuala, 2023)
Objective This study aims to delve into the factors that impact consumers' purchase intention when shopping on the platform, namely Live Streaming Shopping Attributes, Low Price Appeal, Trust in Sellers, and a Guarantee Return Policy as a moderating variable.Methodology The research design includes a survey of 170 participants selected through purposive sampling and analyzed using PLS-SEM statistical analysis.Results The results of this study show that Live Streaming Shopping Attributes and Low-Price Appeal significantly impact purchase intention, and that Guarantee Return Policy plays a significant role in moderating their effects. The findings of this study will provide valuable insights for companies and managers looking to increase purchase intention through live-streaming shopping.Novelty/Originality This study breaks new ground by using the Guarantee Return Policy as a moderating variable, whereas prior studies have only explored it as a mediating factor.